Pengaruh Green Accounting, Kinerja Lingkungan Dan Likuiditas Terhadap Profitabilitas - Inas Atikah; Usman Sastradipraja (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Apart from maximizing profits, companies also must pay attention to the environment as a result of the activities carried out by the company. The purpose of this study was to determine the effect of green accounting, environmental performance, and liquidity on probability. The population in this study were Consumer Goods Sector Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2018-2022, totaling 50 samples. Data collection techniques using documentation techniques using secondary data in the form of company annual reports and sustainability reports. This study uses multiple linear analysis techniques. Partial test results show that green accounting and environmental performance do not affect profitability, while liquidity affects probability. In simultaneous testing, the results showed that green accounting, environmental performance, and liquidity together did not affect probability. Keywords: Green Accounting, Environmental Performances, Liquidity, Probability, PROPER Rating